2016
DOI: 10.1364/oe.24.015232
|View full text |Cite
|
Sign up to set email alerts
|

Vector Hermite-Gaussian correlated Schell-model beam

Abstract: A new kind of partially coherent vector beam named vector Hermite-Gaussian correlated Schell-model (HGCSM) beam is introduced as a natural extension of recently introduced scalar HGCSM beam. The realizability and beam conditions for a vector HGCSM beam with uniform state of polarization (SOP) or non-uniform SOP are derived, respectively. Furthermore, analytical formulae for a vector HGCSM beam propagating in free space are derived, and the propagation properties of a vector HGCSM beam with uniform SOP or non-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…However, vectorial fields corresponding to other intensity profiles may provide the additional exotic properties. For examples, vector BG and Hermite-Gaussian have been studied recently to show their distinctiveness [35][36][37]. PV beams provide excellent resistance to the variation of topological charge and the perturbations in propagation, thus, the CVB with PV profile will be fervently desired in applications.…”
Section: Discussionmentioning
confidence: 99%
“…However, vectorial fields corresponding to other intensity profiles may provide the additional exotic properties. For examples, vector BG and Hermite-Gaussian have been studied recently to show their distinctiveness [35][36][37]. PV beams provide excellent resistance to the variation of topological charge and the perturbations in propagation, thus, the CVB with PV profile will be fervently desired in applications.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the sufficient condition for devising genuine correlation functions of partially coherent beams proposed by Gori et al [26,27], Chen et al introduced a class of partially coherent beam with a special spatially correlation function named Hermite-Gaussian correlated Schell-model (HGCSM) beam in 2015 [28]. The propagation properties of the HGCSM beam in free space, focusing optical system, Kolmogorov and non-Kolmogorov turbulent atmosphere have been investigated in detail [28][29][30][31]. It was found that the HGCSM beam exhibits many extraordinary properties, such as self-splitting on propagation in free space, splitting and combining in focusing optical system, and turbulent atmosphere, and selfhealing properties when a portion of the spot is obscured.…”
Section: Introductionmentioning
confidence: 99%
“…Their widespread appeal stems from the fact that, by simply manipulating spatial coherence, the source's resulting shape and polarization can be precisely controlled. Numerous researchers have designed vector partially coherent sources for applications such as free-space and underwater optical communications [7][8][9][10][11][12][13][14][15][16], remote sensing [17,18], optical scattering [19][20][21][22][23][24][25][26][27][28][29], and particle manipulation and trapping [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…The most straightforward and therefore popular design uses a Mach-Zehnder interferometer (MZI) consisting of polarizing beam splitters (PBSs) to split light from a common source into its vertical and horizontal polarization components [5,6,11,[34][35][36][37][38][39]. In each leg of the MZI, the amplitude (beam shape) and coherence of each field component are controlled using absorbing (amplitude) filters and ground-glass diffusers [6,[30][31][32][33]35,36,40,41] or spatial light modulators (SLMs) [5,11,34,37,38,42,43], respectively. While intuitive, the use of separate optical components to control beam shape and coherence complicates the optical setup (alignment, system footprint or size, et cetera) and limits the types of vector partially coherent sources that can be generated (the system's flexibility).…”
Section: Introductionmentioning
confidence: 99%